Protein kinase inhibitors that inhibit induction of lytic program and replication of Epstein-Barr Virus - Goswami, R. (2012)
Signaling pathways mediating Epstein-Barr virus (EBV) reactivation by Ag-bound B-cell receptor (BCR) were analyzed using a panel of 80 protein kinase inhibitors. Broad range protein kinase inhibitors Staurosporin, K252A, and PKC-412 significantly reduced the EBV genome copy numbers measured 48 hours after reactivation perhaps due to their higher toxicity. In addition, selected inhibitors of the phosphatidylinositol-3-kinase (PI3K), protein kinase C (PKC), mitogen-activated protein kinase (MAPK) and nuclear factor κB (NF-κB) pathways, glycogen synthase kinase 3β (GSK-3β), platelet-derived growth factor receptor-associated tyrosine kinase (PDGFRK), and epidermal growth factor receptor-associated tyrosine kinase (EGFRK) significantly reduced the EBV genome copy numbers as well. Of those, only U0126 and Erbstatin analog, which inhibit MAPK pathway and EGFRK respectively, did not inhibit viral reactivation assessed by expression of the EBV early protein, EA-D. None of the tested compounds, except for K252A, affected the activity of the EBV-encoded protein kinase in vitro. These results show that EBV reactivation induced by BCR signaling is mainly mediated through PI3K and PKC, whereas MAPK might be involved in later stages of viral replication.